ANALISIS KUALITAS PELAYANAN DI PPMKP CIAWI BOGOR THE ANALYSIS OF SERVICE QUALITY AT PPMKP CIAWI BOGOR - Muhamad Adi Saputra; Beddy Iriawan Maksudi; Denny Hernawan (Jurnal Governansi, 2016)
The research aim is to know service quality at Pusat  Pelatihan Manajemen  Dan Kepemimpinan Pertanian  (PPMKP) Ciawi Bogor, whether has been achieved optimally or not.            Research methode used is descriptive method, while literture study, observation, and questionnaire are used as tools to collect data.             Based on analysis result reveal that overall score of service quality delivered by PPMKP is classified as “good”, overall score based on employee’s perception is 3,58 (in scale of 5) while based on participant (trainee) overall score is 3,61. It is worth note that detailed score of each dimension of serive quality (tangibles, reliability, responsiveness, assurance, and emphaty) is also quite similar in terms of Weight Mean Score among those respondents (employee and trainee.            Based on analysis result, important point to be considered as recommendation to Pusat  Pelatihan Manajemen  Dan Kepemimpinan Pertanian  (PPMKP) Ciawi Bogor are : increasing the competence of employee as well as improving training infrastructure.Keywords: Service quality, competence, dimension of service quality